Moderating Influence of Efficiency on Variables of Hospital Financial Performance : Evidence from Indian Multi -Specialty Private Sector Hospitals - Prathibha Patel, M.; Ranjith, V. K. (Indian Journal of Finance, 2018)
Globally, studies that situate financial and non-financial indicators as antecedents to hospital financial performance are a widely-researched domain. Similarly, studies that have investigated hospital efficiency using multiple operational inputs and outputs abound. In this study, however, there was an attempt to explore the intervening effects of hospital efficiency on the nature and magnitude of the relationship between financial & non-financial ratios and cash-flow from operations (CFFO) as a hospital financial performance indicator in India. In view of the afore-mentioned purpose, this study used multivariate panel-data regression technique on the data gathered from 28 standalone multi-specialty private sector hospitals in India for the time period between the years 2012-2013 to 2014-2015.Predictor variables were selected logically based on prior research findings and regressed against CFFO using a fixed effect model with hospital efficiency condition acting as a moderator. Relative hospital efficiencies were calculated using data-envelopment analysis (DEA) technique. The relative efficiency scores were then converted to binary moderator values. The findings from this study indicated towards a direct positive and significant relation between predictor variables, in particular, debt-equity ratio (DER), capital-employed turnover (CET), net-revenue per patient (NRP), and occupancy rate (OR) with CFFO. Further, this study also found a negative and significant relationship between patient’s average length of stay (ALOS) and CFFO. Furthermore, this study also found that hospital efficiency conditions significantly moderated the relationship between the above mentioned variables in their expected direction of relationship. This study also offered insights into the nature, significance, and managerial implications that emerged from the empirical findings of this study. Hospitals are viewed upon as an important link in the healthcare system that efficiently deliver services to the general public at large in India. Any better understanding of ways to sustain the financial health of such indispensable entities is of high-priority.